Determinants of sexual and reproductive health knowledge and attitudes of pre-service teachers - Santos, Maria Sylvia De Santos (College of Education, University of the Philippines Diliman, 2020)
The research aimed to determine the level of, the determinants, and the correlation of sexual and reproductive health knowledge and sexual attitudes of 175 pre-service teachers. A researcher-made questionnaire was use to gather data on sexual and and RH knowledge and sexual attitude. A true, false, do not know/not sure statements for sexual knowledge and a five-point Likert scale for sexual attitudes were used. Data was analyzed using the R programming language software, specifically linear regression analysis and Pearsons correlation coefficient. Result showed that the total mean of the correct answers of the participants was only 62%. Majority of the participants had neutral sexual attitudes. Linear regression analysis showed that the sexual and reproductive health knowledge scores were minimally influenced by the age, college course, alcohol use and multiple sources of information. Sexual attitudes were minimally influenced by biological sex, going to clubs or parties, alcohol use, religion, and film/videos and peers as sources of information. Correlation between sexual knowledge and sexual attitudes was not statistically significant. Based on the results, it is recommended that the sexual and RH education at the university level be enhanced. A similar study with with a higher sample size will also of benefits.